Peran Pemerintah Provinsi Sumatera Barat dalam Penertiban Pertambangan Batuan di Nagari Sikabu Kecamatan Lubuk Alung Kabupaten Padang Pariaman - Imelda Febri Zalmi Putri; Afriva Khaidir (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
This study aims to analyze the role of the West Sumatra Provincial Government in Control of Rock Mining in Sikabu village, Lubuk Alung sub-district, District of Padang Pariaman. As a background of this research is founded that the high level of rock mining exploitation activities in the form of landfill and sirtukil excavation had an impact on road and bridge infrastructure causing damage and disconnection of transportation routes around the mining area, while there was no improvement to the infrastructure. The focus of this research is how to control rock mining in the site. The role of the provincial government in controlling rock mining, and the factors that influence the role of the provincial government in controlling rock mining. The research is a qualitative research with a descriptive method. Data obtained through observation, interviews, and documentation study. The data validity test was done by using source triangulation technique. Data processing techniques with data reduction, data presentation and drawing conclusions. The results of this study indicate that the role of the West Sumatra provincial government which is part of an integrated regional law enforcement team (in accordance with the Decree of the Governor of West Sumatra Province Number 332-107-2019), is not running effectively because the role of the government as information is not well implemented. The lack of mining raids carried out by the government has an impact on the low level of community awareness. Many communities deliberately avoid mining raids which are only occasionally carried out by the government. In fact, this mining raid aims to provide socialization to the community about the importance of environmental balance in exploiting rock mines. Several factors that influence the role of the provincial government in controlling rock mining in the village of Sikabu are among others: a) Disparity of vision and mission among agencies that are members of the integrated regional law enforcement team. b) Limitation of provincial government budget for mining raids.